Sexual Dysfunction in Schizophenia Patients - Yustika Izziyatu Anindita; Erikavitri Yulianti (Universitas Muhammadiyah Palu, 2025)
Sexual dysfunction (SD) is a significant but often overlooked complication among patients with schizophrenia, with a global prevalence of 56.4%—55.7% in men and 60.0% in women. SD in this population is generally caused by both the symptoms of schizophrenia and the side effects of antipsychotic treatment, leading to diminished motivation for intimacy and potential disruption of marital relationships. Despite its impact on quality of life, SD remains underdiagnosed and stigmatized in clinical practice. This literature review aims to explore the general aspects of sexual dysfunction, its various types in patients with schizophrenia, and potential treatment strategies based on current clinical guidelines and considerations. The review was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method. Findings show that the global incidence of sexual dysfunction among schizophrenia patients increased by over 65% between 1990 and 2019, affecting an estimated 941,000 to 1.3 million individuals, primarily due to antipsychotic use. Management strategies include reducing antipsychotic dosages or switching to prolactin-sparing medications, with aripiprazole being the most frequently recommended option.